NEED ANALYSIS OF ENGLISH FOR TOUR AND TRAVEL DEPARTMENT OF VOCATIONAL HIGH SCHOOL IN BENGKULU CITY - Rahamdina Salisna; Alamsyah Harahap; Dedi Sofyan (JOALL (Journal of Applied Linguistics and Literature), 2019)
This research aimed to investigate the English needs of Tour and Travel Department at Vocational High School Negeri 1 and Vocational High School Negeri 7 in Bengkulu City. The research used mixed method and convergent parallel design. The sample of this research consisted of three groups of respondents. First group was students, consisted of 28 active students and 4 alumni. Second group was English teachers, consisted of 2 English teachers. The third group was stakeholders, consisted of two heads of the Tour and Travel Department, two assistances of curriculum, hotel, and tour staffs. The data of this research were gathered by using adapted questionnaire and interview. The questionnaire was analyzed quantitatively and interview was analyzed qualitatively. The data were combined by using convergent parallel design. Results of this research indicated that listening and speaking are the two prioritized skills needed by the tour and travel department. Topics of speaking which has the greatest importance are flight reservation, prices and payment, tourist destination, tourist attraction, direction, and booking hotels. Topics of listening which has the greatest importance are flight reservation, booking hotels, direction, job interview, complaints, and cultural tourism.  Topics of reading which has the greatest importance are memos, letters, cultural tourism, handling a complaint, and tourism terms. Topics of writing which has the greatest importance are rules and regulation, instruction.